GROWTH AND DEVELOPMENTIN CHILDREN- AN AYURVEDA REVIEW (AYUSHDHARA, 2019)
The emotional, social and physical development of young children has a direct effect on their overall development and on the adult, they will become. That is why understanding the need to invest in very young children is so important, so as to maximize their future well-being. From above description it is very clear that, childhood is very crucial time period of life, therefore, Ayurveda Acharyas have very well identified the importance of child growth and development and differentiated the health and diseases of children from adult. Ayurveda has established the independent branch for child rearing practices and treatment of childhood diseases and named as Kaumarabhritya. Acharya Kashyapa has described the care of the child right from the gestational age during pregnancy, during labour and after the birth up to the age of sixteen years of life. If one closely observed the chapters of Kashyapa Samhita keenly, one can find a central theme behind all the principles of Ayurveda practices. That central theme is the growth of baby. All the Samskara mentioned in Ayurveda, are child rearing measures and treatment protocols focusing on the growth of baby, and planned systematically without hampering or altering the growth of the child. Also, growth assessment in children has been very well described by Ayurveda acharyas.